Carbon fiber composite material
Patent Information
- Application Number
- JP2022130348
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-09-15
- Filing Date
- 2022-08-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-08-18
AI Technical Summary
Conventional carbon fiber composite materials lack sufficient impact resistance due to inadequate strain energy density, strand strength, and elongation, with existing techniques failing to balance these properties effectively.
A carbon fiber composite material is developed with specific properties: strand strength of 7.5 to 8.5 GPa, elongation of 2.65 to 3.20%, single fiber diameter of 4.0 to 6.0 μm, and a strain energy density of 95 J/mm³, achieved through controlled production processes including polyacrylonitrile-based precursor fibers, dry-wet spinning, and optimized epoxy resin composition.
The composite material exhibits enhanced impact resistance and energy absorption, with improved strain energy density, making it suitable for applications requiring high impact resistance and lightweight components.
Abstract
Description
[Technical Field]
[0001] This invention relates to a highly elongated carbon fiber composite material, which is obtained by combining highly elongated carbon fibers with excellent energy absorption properties and an epoxy resin composition that maximizes those properties. [Background technology]
[0002] Polyacrylonitrile-based carbon fibers are lightweight, high-strength, and high-modulus materials, making them indispensable for reducing the weight of components. Furthermore, a key characteristic of carbon fibers is that their deformation is elastic, not plastic. Therefore, carbon fibers have the advantage of a larger usable elongation range compared to metals, which exhibit significant plastic deformation.
[0003] In recent years, carbon fiber composite materials are sometimes required to achieve both lightness and impact resistance. To meet this requirement, the composition design of the resin used in the matrix and sizing agents to alter the interfacial properties between the carbon fibers and the matrix resin are being investigated.
[0004] Attempts to improve the strand strength or strand elongation of carbon fibers have been made in the past. Patent Document 1 describes how to obtain carbon fibers with a maximum strand strength of 9.0 GPa (Example 8) by reducing defects through fine denierization of precursor fibers. Patent Document 2 similarly describes how to obtain carbon fibers with a maximum strand strength of 8.0 GPa (Example 14) and elongation of 2.60% (Comparative Examples 4 and 5) by fine denierization of precursor fibers and subsequent stretching. Patent Document 3 describes how to obtain carbon fibers with a maximum strand strength of 8.4 GPa (Example 3) by increasing the fracture toughness of the carbon fibers. Patent Document 4 describes how to obtain carbon fibers with a maximum elongation of 2.68% (Example 15) using a technique that does not significantly reduce strand strength even when the single fiber diameter of carbon fibers is increased. Patent Document 5 aims to increase elongation by adjusting manufacturing conditions such as polymerization, yarn production, and flame resistance, and has obtained carbon fibers with a maximum elongation of 2.36% (Example 1). Patent Document 6 describes how to maximize the elongation of carbon fibers by lowering the maximum temperature of the carbonization process, thereby obtaining carbon fibers with a maximum elongation of 2.60% (Example 4). Patent Document 7 describes how to obtain high-strength, high-elongation carbon fibers by adjusting the surface properties of the carbon fibers, but the elongation of the carbon fibers is only about 2.1%, which is the general level of technology for high-strength carbon fibers. Patent Document 8 describes how to obtain carbon fibers with a maximum elongation of 2.71% (Example 4) by adding boron to the polymer.
[0005] Furthermore, as part of studies to improve the impact resistance of carbon fiber composite materials, Patent Document 9 describes adding a modifier to the thermoplastic resin matrix.
[0006] In Patent Document 10, the impact resistance, tensile strength, and compressive strength of the carbon fiber composite material are enhanced by adjusting the rubbery plateau modulus above the glass transition point. In Patent Document 11, the interlaminar toughness and compressive strength of the carbon fiber composite material under high-temperature environments are enhanced by adjusting the rubbery plateau modulus above the glass transition point. In Patent Document 12, the compressive strength of the carbon fiber composite material is enhanced by adjusting the compressive yield stress of the cured resin. In Patent Document 13, the tensile strength of the perforated plate of the carbon fiber composite material is enhanced by combining carbon fibers having a specific single fiber strength with an epoxy resin composition having a specific composition.
Prior Art Documents
Patent Documents
[0007]
Patent Document 1
Patent Document 2
Patent Document 3
Patent Document 4
Patent Document 5
Patent Document 6
Patent Document 7
Patent Document 8
Patent Document 9
Patent Document 10
Patent Document 11
Patent Document 12
Patent Document 13
[0008] However, conventional technologies have the following challenges:
[0009] In the technology described in Patent Document 1, the single fiber diameter of the carbon fiber is small, resulting in low strain energy per single fiber. In addition, the strand modulus of elasticity is high and the elongation is low, which prevents sufficient impact resistance from being ensured in a bending stress field.
[0010] The technology described in Patent Document 2 had problems in that the diameter of the carbon fibers was small, resulting in low strain energy per fiber, and in addition, satisfactory elongation could not be obtained.
[0011] The technology described in Patent Document 3 has the problem of not being able to obtain satisfactory elongation, and furthermore, due to the high modulus of elasticity of the strand, sufficient impact resistance could not be ensured in the bending stress field.
[0012] The technology described in Patent Document 4 had insufficient levels of strand strength and elongation, and therefore could not ensure sufficient impact resistance. Furthermore, it did not anticipate the need to achieve both strand strength and elongation simultaneously.
[0013] The technology described in Patent Document 5 did not ensure sufficient impact resistance.
[0014] In the technology described in Patent Document 6, the strand modulus level was too low, and sufficient impact resistance could not be ensured.
[0015] The technology described in Patent Document 7 had an excessively low elongation level, which prevented it from ensuring sufficient impact resistance.
[0016] While the technology described in Patent Document 8 increases the elongation of carbon fibers, strands with high elongation have low strand strength, and because the concept of strain energy density was not considered, it was not anticipated that both strand strength and elongation could be achieved simultaneously.
[0017] Thus, until now, there had been no carbon fiber that satisfied all the requirements of single fiber diameter, strand strength, and elongation.
[0018] Furthermore, while Patent Document 9 describes the compositional design of thermoplastic resins for the impact resistance of carbon fiber composite materials, it does not mention the mechanical properties of the carbon fibers themselves.
[0019] While Patent Documents 10-12 design the mechanical properties of epoxy resin cured products to maximize the mechanical properties of existing carbon fibers, they do not focus on the elongation of carbon fiber composite materials, and the level of elongation achieved is not satisfactory.
[0020] Although Patent Document 13 improved the tensile strength of perforated carbon fiber composite materials not only by the strength of the single carbon fibers but also by combining them with a specific epoxy resin composition, the elongation of the carbon fiber composite material was not at a satisfactory level.
[0021] The present invention aims to provide a carbon fiber composite material that improves impact resistance. [Means for solving the problem]
[0022] To achieve the above objectives, the carbon fiber composite material of the present invention comprises carbon fibers having a strand strength of 7.5 to 8.5 GPa, an elongation of 2.65 to 3.20%, and a single fiber diameter of 4.0 to 6.0 μm, and an epoxy resin composition having an amine-type epoxy resin [A], a thermoplastic resin [B] that dissolves in the epoxy resin, and an epoxy resin curing agent [C], wherein the degree of curing of the epoxy resin composition is 90% or more, and the storage modulus of elasticity at 275°C is measured at a rate of 5°C / min using a dynamic viscoelasticity measuring device according to SACMA SRM 18R-94 and in a torsional mode of 1.0 Hz, and is 1 to 10 MPa. [Effects of the Invention]
[0023] By using the carbon fiber composite material of the present invention, the impact resistance, expressed as strain energy density, of the carbon fiber composite material can be improved. [Modes for carrying out the invention]
[0024] The inventors focused on the strain energy density of carbon fibers in order to improve the impact resistance of carbon fiber composite materials. Strain energy density is the area of the stress-strain curve obtained by tensile property testing of resin-impregnated strands (hereinafter sometimes abbreviated as strands). However, since it is difficult to accurately calculate the nonlinearity, the present invention uses the above-mentioned strand strength (MPa = J / mm²). 3 The approximate value obtained by dividing the product of (strand strength) and elongation (-) by 2 is defined as the strain energy density. In other words, the strand strength and elongation of the carbon fiber are important. A high strain energy density of the carbon fiber can be expected to improve the impact resistance of the resulting carbon fiber composite material.
[0025] The carbon fiber of the present invention has a strand strength of 7.5 to 8.5 GPa, preferably 7.8 to 8.5 GPa, and more preferably 8.0 to 8.5 GPa. Strand strength is an index indicating the resistance of carbon fiber to fracture when a load is applied. The strand strength of carbon fiber can be evaluated according to the tensile test of resin-impregnated strands described in JIS R7608:2004. A strand strength of 7.5 GPa or higher makes it easier to increase the strain energy density. There is no upper limit to the strand strength, but a strength of 8.5 GPa is usually sufficient to achieve a satisfactory level of strain energy density. Strand strength can be controlled by manufacturing according to the carbon fiber manufacturing method described later, which includes defect suppression and improvement of fracture toughness.
[0026] The carbon fiber of the present invention has an elongation of 2.65% or more, preferably 2.75% or more, more preferably 2.85% or more, and even more preferably 2.95% or more. The elongation of the carbon fiber can be evaluated according to the tensile test of resin-impregnated strands described in JIS R7608:2004. Measuring the elongation of carbon fiber is difficult because the stress-strain curve exhibits nonlinearity, but in this tensile test, the elongation is calculated by dividing the strand strength by the strand modulus of elasticity. An elongation of 2.65% or more makes it easier to increase the strain energy density. There is no upper limit to the elongation, but 3.20% is often sufficient to increase the strain energy density. The elongation of the carbon fiber can be adjusted by controlling the manufacturing conditions of the carbon fiber to achieve a balance between strand strength and strand modulus of elasticity.
[0027] The carbon fiber of the present invention has a single fiber diameter of 4.0 to 6.0 μm, preferably 4.5 μm or more, more preferably 5.0 μm or more, and even more preferably 5.3 μm or more. Since the breaking load per single fiber is determined from the strand strength and the single fiber cross-sectional area, the single fiber diameter affects the breaking load per single fiber. Furthermore, the larger the single fiber diameter, the higher the single fiber compressive strength of the carbon fiber tends to be, and the greater the energy absorption. Therefore, if the single fiber diameter is 4.0 μm or more, energy absorption tends to be greater. As an upper limit for the single fiber diameter, 6.0 μm is often sufficient to ensure adequate impact resistance. The single fiber diameter of the carbon fiber can be calculated from the total fineness, density, and number of filaments of the carbon fiber. If the number of filaments is unknown, the carbon fiber can be embedded in resin, the cross-section can be observed with an optical microscope, the cross-sectional area of the single fiber can be determined by image processing, and this can be calculated as the equivalent diameter of a circle to evaluate the single fiber diameter. If the two measurement methods do not match, the former value should be adopted. The single fiber diameter can be controlled by the diameter of the precursor fiber and the stretching ratio in subsequent processes.
[0028] The carbon fiber of the present invention preferably has a strain energy density of 95 J / mm². 3 The above is more preferable, 100 J / mm 3The above is preferable to 105 J / mm 3 That concludes the explanation. The strain energy density is 95 J / mm². 3 If the energy absorption is above this level, it is often sufficient, and there is no upper limit, but 140 J / mm 3 In some cases, the value of energy absorption may be saturated due to its balance with other properties. Strain energy density can be adjusted by controlling the manufacturing conditions of the carbon fiber to achieve both strand strength and elongation.
[0029] The carbon fiber of the present invention preferably has a strand modulus of 240 to 300 GPa, more preferably 250 to 290 GPa, and even more preferably 250 to 280 GPa. The strand modulus is an index indicating the resistance of carbon fiber to deformation when a load is applied. The strand modulus of carbon fiber can be evaluated according to the tensile test of resin-impregnated strands described in JIS R7608:2004. Although the stress-strain curve of carbon fiber shows a downward convex nonlinearity, the present invention uses the strand modulus in the strain range of 0.1 to 0.6%. If the strand modulus is 240 GPa or higher, the strain energy density is easily increased. If the strand modulus is 300 GPa or lower, the compressive strength of the carbon fiber is high and energy absorption is high. The strand modulus can be controlled by the maximum temperature of the carbonization process, the heat treatment time at the maximum temperature, the heating rate, the stretch ratio, etc.
[0030] The carbon fiber of the present invention preferably has a total fineness of 0.8 g / m or more, more preferably 0.9 g / m or more. The total fineness is the mass per 1 m of the fiber bundle of the carbon fiber and is related to the single fiber diameter and the number of filaments of the carbon fiber. The higher the total fineness, the easier it is to increase the productivity of the carbon fiber composite material. Therefore, if the total fineness is 0.8 g / m or more, an excellent impact-resistant carbon fiber composite material can be obtained with good productivity. If the total fineness is 2.0 g / m or less, a carbon fiber composite material with an appropriate thickness can be obtained, and as a result, the impact resistance can be increased, which is preferable. The total fineness can be controlled by adjusting the single fiber diameter or the number of filaments, but if the number of filaments is too large, uniform production becomes difficult and the strand strength tends to decrease.
[0031] The carbon fiber of the present invention preferably has a density of 1.75 to 1.85 g / cm 3 . The greater the density of the carbon fiber, the denser the fine structure and the easier it is for the strand strength to increase. Therefore, if the density is 1.75 g / cm 3 or more, the energy absorption tends to reach a satisfactory level, and if it is 1.85 g / cm 3 or less, the elongation is high and the energy absorption is likely to be maintained at a high level. The lower limit of the density is more preferably 1.78 g / cm 3 . The upper limit of the density is more preferably 1.83 g / cm 3 . The density of the carbon fiber can be controlled by the draw ratio and the heating rate in the carbonization process.
[0032] Next, a method for producing carbon fiber suitable for obtaining the carbon fiber of the present invention will be described.
[0033] As an industrial production method of carbon fiber, there is known a method that includes a flame-retardant treatment step of converting a polyacrylonitrile-based carbon fiber precursor fiber (hereinafter sometimes abbreviated as precursor fiber) into a flame-retardant fiber in an oxidizing atmosphere at 200 to 310°C, a pre-carbonization step of pre-carbonizing in an inert atmosphere at 500 to 1,200°C, and a carbonization step of carbonizing in an inert atmosphere at 1,000 to 1,500°C.
[0034] A polyacrylonitrile polymer is preferably used as a raw material for the production of precursor fibers. In this invention, the polyacrylonitrile polymer is a polymer in which at least acrylonitrile accounts for 90 to 100 mol% of the polymer. In the production of precursor fibers, the polyacrylonitrile polymer preferably contains copolymer components from the viewpoint of improving strand strength. As monomers that can be used as copolymer components, monomers containing one or more carboxylic acid groups or amide groups are preferably used from the viewpoint of promoting flame resistance.
[0035] In producing precursor fibers, either a wet-dry spinning method or a wet spinning method may be used, but it is preferable to use a wet-dry spinning method, which is advantageous for the strand strength of the resulting carbon fibers. The spinning process consists of a spinning step in which a spinning solution is discharged from a spinneret into a coagulation bath using a wet-dry spinning method, a washing step in which the fibers obtained in the spinning step are washed and stretched in a water bath, and a drying heat treatment step in which the fibers obtained in the washing step are dried and heat treated. Preferably, a steam stretching step is included in which the fibers obtained in the drying heat treatment step are steam stretched. The order of each step can also be changed as appropriate. The spinning solution is obtained by dissolving the aforementioned polyacrylonitrile polymer in a polyacrylonitrile-soluble solvent such as dimethyl sulfoxide, dimethylformamide, and dimethylacetamide.
[0036] The coagulation bath preferably contains a solvent such as dimethyl sulfoxide, dimethylformamide, and dimethylacetamide, which were used as the solvent for the spinning solution, and a so-called coagulation promoting component. As the coagulation promoting component, one that does not dissolve the polyacrylonitrile polymer and is compatible with the solvent used for the spinning solution can be used. Specifically, it is preferable to use water as the coagulation promoting component.
[0037] In the aforementioned washing process, it is preferable to use a washing bath consisting of multiple stages with a temperature of 30 to 98°C. Furthermore, the stretching ratio in the washing process is preferably 2 to 6 times. Subsequently, in order to improve the strand strength, an oil agent consisting of silicone or the like is preferably applied to the fibers. Such a silicone oil agent preferably contains amino-modified silicone.
[0038] The drying heat treatment process can utilize known methods. For example, a drying temperature of 100-200°C is exemplified.
[0039] After the aforementioned washing and drying heat treatment steps, if necessary, steam stretching is performed to obtain precursor fibers suitable for obtaining the carbon fibers of the present invention. Steam stretching is performed in pressurized steam, with a stretching ratio of preferably 2 to 6 times.
[0040] To increase the strand strength of carbon fibers, the flame-retardant fibers obtained in the flame-retardant process must have an infrared spectrum of 1,370 cm⁻¹. -1 1,453 cm⁻¹ for peak intensity -1 The ratio of peak intensities is in the range of 0.70 to 0.75, and the infrared spectrum is 1,370 cm⁻¹. -1 1,254 cm⁻¹ for peak intensity -1 It is preferable to control the ratio of the peak intensities so that it is in the range of 0.50 to 0.65. In the infrared spectrum, 1,453 cm⁻¹ -1 The peak is of alkene origin and decreases as flame resistance progresses. 1,370 cm -1 The peak is 1,254 cm. -1 The peak is due to the flame-retardant structure and increases as flame resistance progresses. Note that a standard flame-retardant fiber with a specific gravity of 1.35 has a specific gravity of 1,370 cm². -1 1,453 cm⁻¹ for peak intensity -1 The ratio of peak intensities is approximately 0.63 to 0.69, indicating that in the flame-retardant process of the present invention, it is preferable for the resulting flame-retardant fibers to retain more alkene-derived structures than usual. 1,370 cm -11,254 cm⁻¹ for peak intensity -1 The ratio of peak intensities decreases as flame resistance progresses, with a particularly large decrease in the initial stages. However, depending on the flame resistance conditions, the peak intensity ratio may not fall below 0.65 even with increased time.
[0041] To achieve a balance between these two peak intensity ratios within the desired range, the conditions should primarily focus on setting the parameters such as a low amount of copolymer components in the polyacrylonitrile polymer constituting the precursor fiber, a high degree of crystal orientation in the precursor fiber, a low single-fiber fineness in the precursor fiber, and a high flame-retardant temperature in the later stages. Specifically, the flame-retardant process should be set to the 1,370 cm⁻¹ range in the infrared spectrum. -1 1,453 cm⁻¹ for peak intensity -1 A first flame-retardant step involves flame-retarding the fibers for 8 to 25 minutes, preferably 8 to 15 minutes, until the ratio of peak intensities is in the range of 0.98 to 1.10, and then measuring the 1,370 cm⁻¹ of the infrared spectrum of the fibers obtained in the first flame-retardant step. -1 1,453 cm⁻¹ for peak intensity -1 The ratio of peak intensities is in the range of 0.70 to 0.75, and the infrared spectrum is 1,370 cm⁻¹. -1 1,254 cm⁻¹ for peak intensity -1 It is preferable to carry out this process in two stages: a second flame-retardant treatment for 5 to 14 minutes, preferably 5 to 10 minutes, until the peak intensity ratio is in the range of 0.50 to 0.65.
[0042] In the first flame-retardant treatment step, the flame-retardant temperature is preferably set to 200-250°C, more preferably 230-250°C, in order to control the infrared spectrum within the range described above.
[0043] The flame-retardant temperature in the second flame-retardant process is higher than that of the first flame-retardant process. To shorten the flame-retardant time in the second flame-retardant process, the flame-retardant temperature should be adjusted to a higher temperature, but the appropriate flame-retardant temperature depends on the properties of the precursor fiber. It is preferable to set the flame-retardant temperature to 280-310°C, more preferably 280-300°C, and even more preferably 285-295°C in order to control the infrared spectrum within the range described above. The flame-retardant temperature does not need to be constant, and a multi-stage temperature setting is also acceptable. To increase the strand strength of the resulting carbon fiber, it is preferable to set a high flame-retardant temperature and a short flame-retardant time.
[0044] In this invention, flame-retardant treatment refers to heat-treating the precursor fibers in an oxygen-containing atmosphere at 200-310°C.
[0045] The flame-retardant time referred to here means the time the fibers remain in the flame-retardant furnace. Flame-retardant fibers refer to fibers after the flame-retardant process but before the pre-carbonization process. The peak intensity referred to here is the absorbance at each wavelength after baseline correction of the spectrum obtained by measuring the infrared spectrum of a small sample of flame-retardant fibers; no peak splitting is performed. The sample concentration for infrared spectrum measurement is diluted with KBr to 0.67 mass%. In this way, the infrared spectrum should be measured each time the flame-retardant conditions are changed, and the conditions should be investigated according to the preferred manufacturing method described later. By appropriately controlling the infrared spectral peak intensity ratio of the flame-retardant fibers, the strand strength of the resulting carbon fibers can be controlled.
[0046] The total processing time for the flame-retardant treatment process can be appropriately selected within the range of preferably 13 to 20 minutes. Furthermore, in order to improve the strand strength of the resulting carbon fiber, the flame-retardant treatment time is set so that the specific gravity of the resulting flame-retardant fiber is preferably in the range of 1.28 to 1.32, more preferably 1.30 to 1.32. A more preferable flame-retardant treatment time depends on the flame-retardant temperature. If the specific gravity of the flame-retardant fiber is less than 1.28, the strand strength of the carbon fiber may decrease. If the specific gravity of the flame-retardant fiber is 1.32 or less, the strand strength can be increased. The specific gravity of the flame-retardant fiber is controlled by the processing time and flame-retardant temperature of the flame-retardant treatment process. Also, the timing for switching from the first flame-retardant treatment process to the second flame-retardant treatment process is preferably when the specific gravity of the fiber is in the range of 1.21 to 1.23. Even in this case, the conditions of the flame-retardant treatment process are controlled prioritizing the satisfaction of the aforementioned range of infrared spectral intensity ratios. The preferred range of flame-retardant treatment time and flame-retardant temperature varies depending on the properties of the precursor fiber and the copolymerization composition of the polyacrylonitrile polymer.
[0047] In the pre-carbonization step, which involves pre-carbonizing the fiber bundles obtained in the flame-retardant process, the obtained flame-retardant fibers are heat-treated in an inert atmosphere at a maximum temperature of 500 to 1,200°C until the specific gravity is preferably 1.5 to 1.8. The stretch ratio in the pre-carbonization step is preferably 1.16 to 1.25. If the stretch ratio in the pre-carbonization step is 1.16 or higher, the strand modulus of elasticity tends to increase, and the strand strength tends to increase. If the stretch ratio in the pre-carbonization step is 1.25 or lower, the strand modulus of elasticity tends to be suppressed to 300 GPa or less.
[0048] Pre-carbonized fibers are carbonized in an inert atmosphere, preferably at a maximum temperature of 1,000 to 1,500°C, more preferably at 1,100 to 1,300°C, and even more preferably at 1,150 to 1,250°C. From the viewpoint of increasing the elongation of the resulting carbon fibers, a lower maximum temperature is preferable for the carbonization process. However, if the temperature is too low, the strand strength may decrease, so it is preferable to set the temperature while considering both factors.
[0049] Furthermore, the processing time X at the highest temperature of the carbonization process is preferably 20 to 60 seconds, and more preferably 20 to 38 seconds. The processing time X at the highest temperature of the carbonization process is the time required for the fibers to pass through the highest temperature section in the carbonization furnace. Carbonization furnaces often have multiple sections in which the temperature is controlled to rise in stages by heater blocks. Each section is considered to be at a constant temperature for calculations. A processing time X of 60 seconds or less is preferable because a shorter processing time at the highest temperature allows for lower control of the strand modulus. A stable strand modulus is easily obtained if the processing time X is 20 seconds or more.
[0050] The heating rate Y in the carbonization process is preferably 0.40 to 1.1°C / second, more preferably 0.40 to 1.0°C / second, and even more preferably 0.40 to 0.60°C / second. The heating rate in the carbonization process affects the strand strength because it affects the decomposition rate of the decomposition gas. In this invention, the heating rate is defined as the average rate in degrees Celsius per second at which the fibers pass through a region where the temperature of a section exceeds 1,000°C, as the fibers pass through a plurality of sections in the carbonization furnace, where the temperature is controlled to increase in stages. Specifically, for example, if the fibers take 100 seconds to pass through the section with a temperature of 1,000°C in the carbonization furnace and reach the next section with a temperature of 1,100°C, the heating rate is 1.0°C / second. In another example, if the fibers pass through the carbonization furnace from the 950°C section to the next 1,150°C section in 200 seconds, the heating rate is 1.0°C / second. Furthermore, when the maximum temperature of the carbonization process is set below 1,100°C, the heating rate up to the maximum temperature is utilized. That is, if the maximum temperature is 1,050°C, and the fibers pass through the carbonization furnace from the 1,000°C section to the next 1,050°C section in 50 seconds, the heating rate is 1.0°C / second. The temperature of the first section in the carbonization furnace is preferably 1,000°C or lower. A heating rate of 0.40°C / second or higher makes it easier to obtain a stable strand modulus. A heating rate of 1.1°C / second or less makes it easier to suppress the decrease in strand strength.
[0051] The processing time X and heating rate Y at the maximum temperature of the carbonization process are preferably in the range of 0.015X ≤ Y ≤ 0.015X + 0.6. This formula was derived from the inventor's research results to increase the elongation of carbon fibers. By adjusting the processing time X and heating rate Y to this relationship, it is easier to increase the elongation of carbon fibers.
[0052] The carbon fibers obtained as described above are preferably further subjected to electrolytic surface treatment to introduce oxygen-containing functional groups. While gas-phase oxidation, liquid-phase oxidation, and liquid-phase electrolytic oxidation can all be used for the electrolytic surface treatment, liquid-phase electrolytic oxidation is preferred from the viewpoint of high productivity and uniform treatment. In this invention, there are no particular restrictions on the method of liquid-phase electrolytic oxidation; any known method may be used.
[0053] After such electrolytic surface treatment, sizing treatment can be performed to impart bundle properties to the resulting carbon fibers. Depending on the type of matrix resin used in the carbon fiber composite material, a sizing agent with good compatibility with the matrix resin can be appropriately selected.
[0054] Next, the carbon fiber composite material of the present invention will be described. The carbon fiber composite material of the present invention comprises the carbon fibers of the present invention described above and an epoxy resin composition [C] having an amine-type epoxy resin [A], a thermoplastic resin that dissolves in the epoxy resin [B], and an epoxy resin curing agent as the matrix resin.
[0055] Examples of the amine-type epoxy resin [A] used in the present invention include tetraglycidyldiaminodiphenylmethane, tetraglycidyldiaminodiphenylsulfone, tetraglycidylxylylenediamine, triglycidylaminophenol, triglycidylaminocresol, diglycidylaniline, diglycidyltoluidine, or halogen-substituted, alkyl-substituted, and hydrogenated versions thereof. Among these, tetraglycidyldiaminodiphenylmethane, triglycidylaminophenol, or halogen-substituted, alkyl-substituted, and hydrogenated versions thereof are preferred because they can impart elastic modulus and heat resistance.
[0056] Commercially available tetraglycidyldiaminodiphenylmethane products include "SumiEpoxy" (registered trademark) ELM434 (manufactured by Sumitomo Chemical Co., Ltd.), YH434L (manufactured by Nippon Steel & Sumitomo Metal Chemical Corporation), "jER" (registered trademark) 604 (manufactured by Mitsubishi Chemical Corporation), "Araldide" (registered trademark) MY720, "Araldide" (registered trademark) MY721, "Araldide" (registered trademark) MY9512, and "Araldide" (registered trademark) MY9663 (all manufactured by Huntsman Advanced Materials).
[0057] Examples of commercially available tetraglycidyldiaminodiphenylsulfone include TG3DAS (manufactured by Mitsui Chemicals Fine, Inc.).
[0058] Examples of commercially available tetraglycidyl xylylenediamine and its hydrogenated products include "TETRAD" (registered trademark)-X and "TETRAD" (registered trademark)-C (both manufactured by Mitsubishi Gas Chemical Company, Inc.).
[0059] Commercially available triglycidylaminophenol or triglycidylaminocresol products include "SumiEpoxy" (registered trademark) ELM100, "SumiEpoxy" (registered trademark) ELM120 (both manufactured by Sumitomo Chemical Co., Ltd.), "Araldide" (registered trademark) MY0500, "Araldide" (registered trademark) MY0510, "Araldide" (registered trademark) MY0600 (all manufactured by Huntsman Advanced Materials), and "jER" (registered trademark) 630 (manufactured by Mitsubishi Chemical Corporation).
[0060] Commercially available diglycidylaniline compounds include GAN (manufactured by Nippon Kayaku Co., Ltd.) and TOREP-E204 (manufactured by Toray Fine Chemicals Co., Ltd.).
[0061] Examples of commercially available diglycidyltoluidine include GOT (manufactured by Nippon Kayaku Co., Ltd.).
[0062] In the present invention, it is preferable that 50 to 100 parts by mass of amine-type epoxy resin [A] are contained in 100 parts by mass of the total amount of epoxy resin, and more preferably in the range of 70 to 100 parts by mass. If the amount of amine-type epoxy resin is less than 50 parts by mass relative to 100 parts by mass of the total amount of epoxy resin blended, the epoxy resin composition may have insufficient heat resistance and elastic modulus. Furthermore, the compressive strength may decrease when used as a carbon fiber composite material.
[0063] The epoxy resin composition of the present invention preferably contains a difunctional amine-type epoxy resin and a trifunctional or higher amine-type epoxy resin as the amine-type epoxy resin [A]. The inclusion of a difunctional amine-type epoxy resin extends the distance between crosslinking points, reducing the storage modulus at 275°C and improving the elongation of the cured epoxy resin. Furthermore, the inclusion of a trifunctional or higher amine-type epoxy resin improves heat resistance and modulus, resulting in a well-balanced resin composition.
[0064] Furthermore, within the limits that do not impair the effects of the present invention, the epoxy resin may contain other epoxy resin components in addition to the amine-type epoxy resin [A]. These may be added in combination, not just one type. An epoxy resin with a weight-average molecular weight of 400 or more is preferably used because it can extend the distance between crosslinking points and reduce the storage modulus at 275°C. Specifically, phenol novolac type epoxy resins, cresol novolac type epoxy resins, resorcinol type epoxy resins, dicyclopentadiene type epoxy resins, urethane and isocyanate-modified epoxy resins, epoxy resins having a biphenyl skeleton, epoxy resins having a fluorene skeleton, and bisphenol type epoxy resins such as bisphenol A type, bisphenol F type, bisphenol S type, bisphenol AD type, or halogen, alkyl-substituted, hydrogenated versions of these bisphenols can be used. Specific examples of such epoxy resins are listed below.
[0065] Commercially available phenol novolac type epoxy resins include "jER" (registered trademark) 152, "jER" (registered trademark) 154 (both manufactured by Mitsubishi Chemical Corporation), "Epiclon" (registered trademark) N-740, "Epiclon" (registered trademark) N-770, and "Epiclon" (registered trademark) N-775 (all manufactured by DIC Corporation).
[0066] Commercially available cresol novolac type epoxy resins include "Epiclon" (registered trademark) N-660, "Epiclon" (registered trademark) N-665, "Epiclon" (registered trademark) N-670, "Epiclon" (registered trademark) N-673, and "Epiclon" (registered trademark) N-695 (all manufactured by DIC Corporation), as well as EOCN-1020, EOCN-102S, and EOCN-104S (all manufactured by Nippon Kayaku Co., Ltd.).
[0067] Specific examples of resorcinol-type epoxy resins include "Denacol" (registered trademark) EX-201 (manufactured by Nagase ChemteX Corporation).
[0068] Commercially available dicyclopentadiene-type epoxy resins include "Epiclon" (registered trademark) HP7200, "Epiclon" (registered trademark) HP7200L, and "Epiclon" (registered trademark) HP7200H (all manufactured by DIC Corporation), Tactix 558 (manufactured by Huntsman Advanced Materials), XD-1000-1L, and XD-1000-2L (both manufactured by Nippon Kayaku Co., Ltd.).
[0069] Commercially available urethane and isocyanate-modified epoxy resins include AER4152 (manufactured by Asahi Kasei E-Materials Corporation) and ACR1348 (manufactured by Asahi Denka Co., Ltd.), both of which have an oxazolidone ring.
[0070] Commercially available epoxy resins containing a biphenyl skeleton include "jER" (registered trademark) YX4000H, "jER" (registered trademark) YX4000, "jER" (registered trademark) YL6616 (all manufactured by Mitsubishi Chemical Corporation), and NC-3000 (manufactured by Nippon Kayaku Co., Ltd.).
[0071] Commercially available epoxy resins containing a fluorene skeleton include ESF300 (manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.), "Oncoat" (registered trademark) EX-1010, "Oncoat" (registered trademark) EX-1011, "Oncoat" (registered trademark) EX-1012, "Oncoat" (registered trademark) EX-1020, "Oncoat" (registered trademark) EX-1030, "Oncoat" (registered trademark) EX-1040, "Oncoat" (registered trademark) EX-1050, and "Oncoat" (registered trademark) EX-1051 (all manufactured by Nagase ChemteX Co., Ltd.).
[0072] Commercially available bisphenol A type epoxy resins include "Epotote" (registered trademark) YD128 (manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.), "jER" (registered trademark) 825, "jER" (registered trademark) 828, "jER" (registered trademark) 834, "jER" (registered trademark) 1001, "jER" (registered trademark) 1004, "jER" (registered trademark) 1007, "jER" (registered trademark) 1009, and "jER" (registered trademark) 1010 (all manufactured by Mitsubishi Chemical Corporation).
[0073] Commercially available bisphenol F type epoxy resins include "Epiclon" (registered trademark) 830, "Epiclon" (registered trademark) 835 (both manufactured by DIC Corporation), "jER" (registered trademark) 806, "jER" (registered trademark) 807, "jER" (registered trademark) 4004P, "jER" (registered trademark) 4007P, "jER" (registered trademark) 4009P, "jER" (registered trademark) 4010P (all manufactured by Mitsubishi Chemical Corporation), and "Epotote" (registered trademark) YDF170, "Epotote" (registered trademark) YDF2001 (both manufactured by Nippon Steel & Sumitomo Metal Chemical Corporation).
[0074] Examples of bisphenol S type epoxy resins include "Epiclon" (registered trademark) EXA-1514 (manufactured by DIC Corporation).
[0075] Examples of bisphenol AD type epoxy resins include "EPOMIK" (registered trademark) R710 and "EPOMIK" (registered trademark) R1710 (both manufactured by Printec Co., Ltd.).
[0076] The epoxy resin composition of the present invention is used by mixing or dissolving a thermoplastic resin [B].
[0077] In the present invention, by combining the above-mentioned amine-type epoxy resin [A] with a thermoplastic resin [B], high toughness can be obtained while avoiding a decrease in heat resistance, and the elongation of the carbon fiber composite material is greatly improved.
[0078] The thermoplastic resin [B] in the present invention is in a crystalline or glassy state at room temperature and is thermoplastic.
[0079] The thermoplastic resin [B] is generally preferably a thermoplastic resin having bonds selected from the group consisting of carbon-carbon bonds, amide bonds, imide bonds, ester bonds, ether bonds, carbonate bonds, urethane bonds, thioether bonds, sulfone bonds, and carbonyl bonds in its main chain. Furthermore, this thermoplastic resin [B] may have a partially crosslinked structure and may be crystalline or amorphous. In particular, it is preferable that at least one resin selected from the group consisting of polyamide, polycarbonate, polyacetal, polyphenylene oxide, polyphenylene sulfide, polyarylate, polyester, polyamideimide, polyimide, polyetherimide, polyimide having a phenyltrimethylindan structure, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyaramid, polyethernitrile, and polybenzimidazole is dissolved in any of the epoxy resins contained in the epoxy resin composition.
[0080] In the present invention, the thermoplastic resin [B] is present in the epoxy resin composition in an amount of 8 to 40% by mass, preferably 8 to 35% by mass, more preferably 12 to 35% by mass, even more preferably 16 to 35% by mass, and most preferably 20 to 30% by mass. If the amount of thermoplastic resin [B] is less than 8% by mass, the toughness of the cured resin decreases, and the interlaminar toughness of the resulting fiber-reinforced composite material is insufficient. If the amount is greater than 40% by mass, the viscosity of the thermosetting resin composition increases, resulting in insufficient manufacturing processability and handling of the thermosetting resin composition and prepreg.
[0081] Furthermore, the weight-average molecular weight of the thermoplastic resin [B] is preferably in the range of 4,000 to 40,000 g / mol, more preferably 10,000 to 40,000 g / mol, and even more preferably 15,000 to 30,000 g / mol. If the weight-average molecular weight is lower than 4,000 g / mol, the elongation and toughness of the cured epoxy resin may be insufficient. If it is higher than 40,000 g / mol, when the thermoplastic resin is dissolved in the epoxy resin composition, the viscosity of the epoxy resin becomes high, making mixing difficult and potentially hindering prepreg formation.
[0082] Furthermore, the glass transition temperature of the thermoplastic resin [B] in the present invention is preferably 150°C or higher, more preferably 200°C or higher, and even more preferably 220°C or higher. If the glass transition temperature of such thermoplastic resin [B] is below 150°C, the carbon fiber composite material may be prone to thermal deformation.
[0083] Examples of such thermoplastic resins [B] include polycarbonate (glass transition temperature (also called Tg): 150°C), polysulfone (Tg: 190°C), polyetherimide (Tg: 215°C), and polyethersulfone (Tg: 225°C). The glass transition temperature of such thermoplastic resins [B] is the glass transition temperature observed when the temperature is increased from 30°C to a temperature 30°C higher than the predicted glass transition temperature at a heating rate of 20°C / min using DSC (differential scanning calorimetry), held for 1 minute, cooled to 0°C at a cooling rate of 20°C / min, held for 1 minute, and then measured again at a heating rate of 20°C / min.
[0084] Commercially available polycarbonate products include "Panlite" (registered trademark) K1300Y (manufactured by Teijin Limited). Commercially available polysulfone products include "Udel" (registered trademark) P-1700, "Udel" (registered trademark) P-3500LCD, and "Virantage" (registered trademark) DAMS VW-30500RP (all manufactured by Solvay Specialty Polymers). Commercially available polyetherimide products include "Ultem" (registered trademark) 1000 and "Ultem" (registered trademark) 1010 (both manufactured by SABIC). Commercially available polyethersulfones include "Sumika Excel" (registered trademark) PES3600P, "Sumika Excel" (registered trademark) PES5003P, "Sumika Excel" (registered trademark) PES5200P, "Sumika Excel" (registered trademark) PES7600P (all manufactured by Sumitomo Chemical Co., Ltd.), "Ultrason" (registered trademark) E2020P SR (manufactured by BASF), "Virantage" (registered trademark) VW-10200RP, and "Virantage" (registered trademark) VW-10700RP (all manufactured by Solvay Specialty Polymers).
[0085] Furthermore, preferred terminal functional groups for this thermoplastic resin [B] include hydroxyl groups, carboxyl groups, amino groups, thiol groups, and acid anhydrides. Examples of thermoplastic resins having hydroxyl groups include polyvinyl acetal resins such as polyvinyl formal and polyvinyl butyral, polyvinyl alcohol, and phenoxy resins. Examples of thermoplastic resins having sulfonyl groups include polyethersulfone.
[0086] Specifically, commercially available phenoxy resins include "Phenotote" (registered trademark) YP-50 and "Phenotote" (registered trademark) YP-50S (both manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.).
[0087] In the present invention, epoxy resin curing agent [C] is a curing agent for the epoxy resin contained in the epoxy resin composition of the present invention, and is a compound having active hydrogen that can react with epoxy groups, and examples include aromatic amines, aliphatic amines, acid anhydrides, and phenols. Specifically, examples of aromatic amines include diaminodiphenylsulfone, diaminodiphenylmethane, diaminodiphenyl ether, diaminobenzanilide, toluenediamine, and diethyltoluenediamine. Among these, diaminodiphenylsulfone or its isomers are preferably used. Diaminodiphenylsulfone or its isomers are preferably used because they can produce epoxy resin cured products with good heat resistance. Examples of diaminodiphenylsulfone isomers include 3,3'-diaminodiphenylsulfone and 4,4'-diaminodiphenylsulfone.
[0088] Liquid diethyltoluenediamine is preferably used in resin transfer molding (RTM) and plutonization molding.
[0089] Examples of aliphatic amine curing agents include isophorone diamine, m-xylenediamine, mensendiamine, and diaminodicyclohexylmethane. Examples of acid anhydrides include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, and succinic anhydride.
[0090] Examples of phenols include phenol novolacs, cresol novolacs, phenol aralkyls, bisphenols such as bisphenol A and bisphenol S, resorcinol, naphthalenediol, and hydroquinone.
[0091] Furthermore, the total amount of the epoxy resin curing agent [C] must be formulated so that the number of moles of active hydrogen contained in [C] is 0.6 to 2.0 times the number of moles of epoxy groups contained in the entire epoxy resin composition. Preferably, this range is 0.6 to 1.0 times for improving the compressive yield stress, and preferably, it is formulated to be 1.1 to 1.8 times, more preferably 1.2 to 1.5 times, for reducing the storage modulus at 275°C. When the number of moles of active hydrogen is 1.0 times or less the number of moles of epoxy groups contained in the entire epoxy resin composition, a high compressive yield stress can be easily obtained because the crosslinking density is high, and when it is 1.1 times or more, the crosslinking density is low, resulting in improved resin elongation. On the other hand, when it exceeds 2.0 times, the heat resistance decreases significantly, and the viscosity of the epoxy resin composition increases, which may make it difficult to produce prepregs.
[0092] Commercially available aromatic amines include Seika Cure S (manufactured by Wakayama Seika Kogyo Co., Ltd.), MDA-220 (manufactured by Mitsui Chemicals, Inc.), “jER Cure” (registered trademark) W (manufactured by Mitsubishi Chemical Corporation), and 3,3'-DAS (manufactured by Mitsui Chemicals Fine, Inc.), “Lonzacure” (registered trademark) M-DEA, “Lonzacure” (registered trademark) M-DIPA, “Lonzacure” (registered trademark) M-MIPA, and “Lonzacure” (registered trademark) DETDA80 (all manufactured by Lonza).
[0093] These epoxy resin curing agents [C] may be used individually or in combination. Alternatively, epoxy resin and epoxy resin curing agents [C], or a portion thereof, can be pre-reacted and incorporated into the composition. This method may be effective for viscosity adjustment and improving storage stability.
[0094] In the present invention, an epoxy resin cured product can be obtained by heating and curing the epoxy resin composition of the present invention under temperature conditions that result in a degree of curing of 90% or more, as determined by DSC. Such temperature conditions can be appropriately set depending on the type and amount of curing agent and accelerator. For example, when diaminodiphenylsulfone is used as the curing agent, a temperature condition of 180°C for 2 hours is suitably used. The degree of curing is calculated from the total heat generation QT of the epoxy resin composition and the residual heat generation QR of the cured product, as determined by DSC (Differential Scanning Calorimetry), using the following formula. Curing degree (%)=(QT-QR) / QT×100.
[0095] In the present invention, the epoxy resin cured product is heated at a rate of 5°C / min using a dynamic viscoelasticity measuring device according to SACMA SRM 18R-94, and the storage modulus at 275°C measured in a torsional mode of 1.0 Hz is 1 to 10 MPa, preferably 5 to 9 MPa, and 6 to 8 MPa. Such a storage modulus is related to the property of suppressing stress concentration when tensile stress is applied to the carbon fiber composite material and single-fiber fracture begins. If such a storage modulus is 1 MPa or higher, the heat resistance of the epoxy resin cured product is sufficient, and if it is 10 MPa or lower, the chain fracture of single fibers due to stress concentration can be suppressed and the elongation of the carbon fiber composite material can be increased.
[0096] In the present invention, the cured epoxy resin composition preferably has a compression yield strain of 10-15%, more preferably 11-15%. The compression yield strain is a parameter related to the degree of crosslinking of the cured epoxy resin, and the lower the degree of crosslinking, the more the strand strength of the carbon fibers can contribute to the 0° tensile strength of the carbon fiber composite material. If the strain is 10% or more, the 0° tensile strength of the carbon fiber composite material is often satisfied, and if the strain is 15% or less, the relationship with the elastic modulus of the cured epoxy resin is often satisfied. Details of such compression measurement will be described later. Since the strain can be controlled mainly by the degree of crosslinking and the distance between crosslinking points, it can be adjusted by the type of epoxy curing agent, the ratio with epoxy resin, the number of epoxy groups in the epoxy resin, etc.
[0097] In the present invention, the cured epoxy resin composition preferably has a compressive yield stress of 90 to 140 MPa, more preferably 95 to 120 MPa, and even more preferably 100 to 110 MPa. This compressive yield stress is related to the interfacial adhesion between the carbon fibers and the epoxy resin cured product. If the compressive yield stress is 90 MPa or higher, the interfacial adhesion strength is often satisfactory, while if it is 140 MPa or lower, the balance with the strain is often excellent.
[0098] In the present invention, the prepreg is obtained by impregnating the above-mentioned epoxy resin composition with the above-mentioned reinforcing fibers. The fiber mass fraction of the prepreg is preferably 40 to 90% by mass, and more preferably 50 to 80% by mass. If the fiber mass fraction is too low, the mass of the resulting composite material will be excessive, which may impair the advantages of carbon fiber composite materials, such as their excellent specific modulus. If the fiber mass fraction is too high, impregnation of the epoxy resin composition will occur, and the resulting carbon fiber composite material is likely to have many voids, which may significantly reduce its mechanical properties.
[0099] The form of carbon fibers is not particularly limited; for example, continuous fiber sheets, tows, fabrics, and mats with fibers aligned in one direction can be used.
[0100] In the present invention, the epoxy resin composition can be produced by a method in which the epoxy resin composition is dissolved in a solvent such as methyl ethyl ketone or methanol to reduce its viscosity and impregnates it into carbon fibers (wet method), or by a hot melt method (dry method) in which the epoxy resin composition is heated to reduce its viscosity and impregnates it into carbon fibers.
[0101] The carbon fiber composite material of the present invention is produced by laminating the obtained prepregs and then heating and curing the epoxy resin composition while applying pressure to the laminate. Here, methods for applying heat and pressure include press molding, autoclave molding, bagging molding, wrapping tape method, and internal pressure molding.
[0102] The carbon fiber composite material of the present invention can be manufactured by a molding method that involves directly impregnating carbon fibers with an epoxy resin composition without using a prepreg, followed by heat curing, such as the hand lay-up method, filament winding method, pultrusion method, resin injection molding method, and resin transfer molding method. In these methods, it is preferable to prepare the epoxy resin composition by mixing two components, a main component made of epoxy resin and an epoxy resin curing agent, immediately before use.
[0103] The carbon fiber composite material of the present invention preferably has a 0° tensile strength of 4.0 GPa or higher, more preferably 4.1 GPa or higher, and even more preferably 4.2 to 4.5 GPa. The 0° tensile strength is an influencing factor for the impact resistance of the carbon fiber composite material. The 0° tensile strength can be evaluated according to JIS K7165 (2008). If the 0° tensile strength is 4.0 GPa or higher, the strain energy density of the carbon fiber composite material is easily increased. There is no upper limit to the 0° tensile strength, but a level of 4.5 GPa is usually sufficient to achieve a satisfactory level of strain energy density for the carbon fiber composite material. The 0° tensile strength can be controlled by the strand strength of the carbon fibers and the storage modulus of the epoxy resin curing product.
[0104] The carbon fiber composite material of the present invention preferably has an elongation of 2.5% or more, and more preferably 2.6 to 2.8%. Such elongation can be evaluated with a strain gauge in accordance with JIS K7165 (2008). If the elongation of the carbon fiber composite material is 2.5% or more, it is easier to increase the strain energy density of the carbon fiber composite material. There is no upper limit to the elongation, but 2.8% is often sufficient to increase the strain energy density of the carbon fiber composite material. The elongation of the carbon fiber composite material can be adjusted by the 0° tensile strength and strand modulus of the carbon fiber composite material. [Examples]
[0105] The methods for measuring various physical properties used in this invention are as follows.
[0106] <Total fiber density> For the carbon fiber to be measured, a 10m length is sampled, and after being completely dried at 120°C for 2 hours, the mass is measured and then divided by 10 to determine the total fineness, which is the mass per meter.
[0107] <density> The carbon fibers to be measured are allowed to air dry at 120°C for 2 hours before measurement. A dry-type automatic densimeter is used to measure density, with nitrogen as the measurement medium and a 10cc sample container. The sample volume is adjusted to 3-6cc. Three measurements are performed, and the average value is used. For this measurement, a Shimadzu AccuPic 1330 dry-type automatic densimeter was used.
[0108] <Single fiber diameter> It is calculated from the total fineness and density obtained, and the number of carbon fiber filaments used in the measurement.
[0109] <Strand strength, strand modulus of elasticity, elongation> The strand strength, strand modulus, and elongation of carbon fiber are determined according to the resin-impregnated strand test method of JIS R7608:2004, following the procedure below. The resin formulation used is "Celoxide" (registered trademark) 2021P (manufactured by Daicel Chemical Industries, Ltd.) / boron trifluoride monoethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) / acetone = 100 / 3 / 4 (parts by mass). The curing conditions are atmospheric pressure, temperature 125°C, and time 30 minutes. The strand strength, strand modulus, and elongation of 10 carbon fiber strands are measured, and the average value is used. The strain range for calculating the strand modulus is 0.1 to 0.6%.
[0110] <Strain energy density of carbon fiber> The strain energy density is calculated using the following formula. Strain energy density (J / mm 3 ) = Strand strength (GPa) × 1,000 × Elongation (%) / 100 / 2.
[0111] <Fabrication of carbon fiber composite materials> (1) Preparation of epoxy resin composition A predetermined amount of amine-type epoxy resin [A] or an epoxy resin other than [A] and thermoplastic resin [B] were added to a kneader and kneaded at a temperature of 150°C or higher to dissolve and obtain a transparent viscous liquid. After the temperature was lowered to 60°C or lower while kneading, predetermined amounts of epoxy resin curing agent [C] and other components were added and kneaded further to obtain an epoxy resin composition.
[0112] In compositions 5 and 6 described later, an epoxy resin composition is obtained by mixing an amine-type epoxy resin [A] or an epoxy resin other than [A] at a temperature of 60°C or higher with a liquid obtained by mixing component [C] at a temperature of 60°C or higher to dissolve the solid component, and then mixing these two liquids at a temperature of 60°C or lower, degassing under vacuum for 1 hour.
[0113] (2) Preparation of prepregs In compositions 1 to 4 described below, an epoxy resin composition is applied to release paper using a knife coater to create a resin film. Next, two resin films are placed on both sides of carbon fibers arranged in a sheet in one direction, and the resin is impregnated into the carbon fibers by heating and pressurizing, resulting in a carbon fiber basis weight of 190 g / m². 2 A unidirectional prepreg is obtained with a mass fraction of 35.5% of the epoxy resin composition.
[0114] (3) Fabrication of RTM laminate For compositions 5 and 6 described later, carbon fiber composite materials were manufactured using the RTM molding method described below.
[0115] Multiple fiber substrates, each with carbon fibers arranged in one direction to achieve a predetermined fiber weight, were laminated and placed on the surface of a flat aluminum mold. A polyester fabric treated with a release agent was then placed on top as a peel ply, followed by a polypropylene knit as a resin diffusion medium. A cavity was then formed by sealing the cavity with a bag material and sealant, except for the resin injection port and a vacuum suction port. The cavity was then vacuumed using a vacuum pump through the vacuum suction port to adjust the vacuum level to -90kPa or lower, after which the mold and preform were temperature-controlled to 70°C. A hot air dryer was used for temperature control. The resin composition was preheated at 70°C for 30 minutes. The preheated liquid resin composition was then set in the resin injection port of the mold, and the thermosetting resin composition was injected into the vacuum cavity using the pressure difference between the cavity pressure and atmospheric pressure, impregnating the arranged fiber substrates. Once the resin composition reached the vacuum suction port, the resin injection port was closed, and suction from the vacuum suction port was maintained for another hour before the vacuum suction port was closed.
[0116] Next, the temperature was raised from 70°C to 140°C at a rate of 1.5°C / min, pre-cured at 140°C for 2 hours, and then cooled to room temperature. The pre-cured product was removed from the mold, and after removing various auxiliary materials such as peel ply, it was raised to 180°C at a rate of 1.5°C / min in a hot air dryer, and then cured at 180°C for 2 hours to obtain a fiber-reinforced composite material (laminated).
[0117] <DSC curing degree measurement of cured resin products> 5 mg of the epoxy resin composition prepared in (1) above is taken, and the temperature is measured from 30°C to 350°C at a heating rate of 10°C / min using a DSC to obtain an exothermic curve. The total heat generation QT of the epoxy resin composition is calculated by integrating the exothermic peaks. In addition, the epoxy resin composition prepared in (1) above is degassed in a vacuum and cured at a temperature of 180°C for 2 hours to obtain a cured epoxy resin product. 5 mg of the obtained cured resin product is taken, and the temperature is measured from 30°C to 350°C at a heating rate of 10°C / min using a DSC to obtain an exothermic curve. If a residual exothermic peak exists, the residual heat generation QR is calculated by integrating that peak. If no residual exothermic peak exists, QR = 0.
[0118] <Glass transition temperature of cured resin and storage modulus at 275°C measured in 1.0 Hz torsional mode> A 10mm wide, 40mm long test piece is cut from a plate of epoxy resin cured material obtained in the same manner as the DSC curing degree measurement of the cured resin material. Using a dynamic viscoelasticity measuring device (ARES: TA Instruments Co., Ltd.), the test piece is set in a solid torsion jig, and measurements are taken in the temperature range of 30 to 300°C at a heating rate of 5°C / min, a frequency of 1Hz, and a strain of 0.1%. At this time, the glass transition temperature is defined as the temperature at the intersection of the tangent line drawn in the glass region and the tangent line drawn in the glass transition region in the obtained storage modulus and temperature graph. The storage modulus at 275°C measured in 1.0Hz torsion mode is defined as the storage modulus at 275°C in the obtained storage modulus and temperature graph. If multiple glass transition temperatures occur, the lowest value is adopted as the glass transition temperature.
[0119] <Compressive yield stress and strain at compressive yield of cured epoxy resin> A 6mm thick epoxy resin cured plate is prepared, and a cubic test specimen with sides of 6mm is cut from the plate. The compressive yield stress and compressive yield strain are measured at a test speed of 1±0.2mm / min, with all other conditions conforming to JIS K7181 (2011).
[0120] <Tensile strength of carbon fiber composite material at 0°> Using the unidirectional prepreg prepared by the method described above, six plies were laminated with the fiber direction aligned, and the laminate was formed in an autoclave at 180°C for 2 hours under a pressure of 0.59 MPa and a heating rate of 1.5°C / min. For the RTM, the fiber content was adjusted using the method described above to be the same as that of the six plies of prepreg, and a laminate was obtained. The 0° tensile strength (GPa) of this laminate was determined according to JIS K7165 (2008). The 0° tensile strength is expressed by converting the measured value to a carbon fiber volume fraction of 60%. Strain was measured using a strain gauge.
[0121] <Strain energy density of carbon fiber composite materials> The strain energy density is calculated using the following formula. Strain energy density (J / mm 3 ) = tensile strength of carbon fiber composite material at 0° (GPa) × 1,000 × strain of carbon fiber composite material (%) / 100 / 2.
[0122] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.
[0123] [Resin raw material] <Amine-type epoxy resin [A]> • "SumiEpoxy" (registered trademark) ELM434 (tetraglycidyldiaminodiphenylmethane, manufactured by Sumitomo Chemical Co., Ltd.) GAN (N,N-diglycidylaniline, manufactured by Nippon Kayaku Co., Ltd.).
[0124] <Epoxy resins other than [A]> • “Epotote” (registered trademark) jER825 (Bisphenol A type epoxy resin, manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.) • “Epiclon” (registered trademark) HP7200L (dicyclopentadiene type epoxy resin, manufactured by DIC Corporation) • "Araldite" AER4152 (epoxy resin containing an oxazolidone ring, manufactured by Asahi Kasei E-Materials Corporation).
[0125] <Thermoplastic resin [B]> • "Sumika Excel" (registered trademark) PES5003P (polyethersulfone, manufactured by Sumitomo Chemical Co., Ltd., weight-average molecular weight: 47,000).
[0126] <Epoxy resin hardener [C]> • Seika Cure S (manufactured by Wakayama Seika Kogyo Co., Ltd.). • “jER Cure” (registered trademark) W (manufactured by Mitsubishi Chemical Corporation) ·3,3'-DAS (Mitsui Chemicals Fine Co., Ltd.).
[0127] [Epoxy resin composition] Using the aforementioned resin raw materials, the mixtures were kneaded according to the compositions shown in Table 1, and their characteristic values are shown (in Table 1, the numbers represent parts by mass). Furthermore, prepregs were prepared for compositions 1 to 4.
[0128] [Carbon Fiber 1] Coagulated yarn was obtained by a wet-dry spinning method, in which a spinning solution containing a polyacrylonitrile copolymer and dimethyl sulfoxide as a solvent was extruded from a spinneret into the air and then introduced into a coagulation bath consisting of an aqueous solution of dimethyl sulfoxide.
[0129] After washing the coagulated yarn with water using a conventional method, it was stretched 3.5 times in two hot water baths. Subsequently, an amino-modified silicone-based silicone oil was applied to the fiber bundle after stretching in the water bath, and a drying and densification treatment was performed using a heated roller at 160°C. After reducing the number of single fibers to 12,000, it was stretched 3.7 times in pressurized steam to achieve a total stretch ratio of 13 times, and then a entanglement treatment was performed to obtain a carbon fiber precursor fiber bundle with a crystal orientation of 93% and 12,000 single fibers. The single fiber fineness of the carbon fiber precursor fiber bundle was 0.7 dtex.
[0130] Next, the carbon fiber precursor fiber bundles were subjected to flame-retardant treatment in an oven under an air atmosphere while being stretched at a stretching ratio of 1. This was done using the conditions of a first flame-retardant treatment at a flame-retardant temperature of 250°C and a flame-retardant treatment time of 11 minutes, and the conditions of a second flame-retardant treatment at a flame-retardant temperature of 280°C and a flame-retardant treatment time of 6 minutes, thereby obtaining flame-retardant fibers.
[0131] Infrared spectrum of the fiber after the first flame-retardant treatment process, at 1,370 cm⁻¹ -1 1,453 cm⁻¹ for peak intensity -1 The ratio of peak intensities was 1.04. Infrared spectrum of the fiber after the second flame-retardant treatment process at 1,370 cm⁻¹ -1 1,453 cm⁻¹ for peak intensity -1 The ratio of peak intensity is 0.70, at 1,370 cm. -1 1,254 cm⁻¹ for peak intensity -1 The ratio of peak intensities was 0.61.
[0132] The obtained flame-resistant fibers were subjected to a pre-carbonization treatment in a nitrogen atmosphere at a maximum temperature of 800°C with a draw ratio of 1.22 to obtain pre-carbonized fibers. The obtained pre-carbonized fibers were then subjected to a carbonization treatment in a nitrogen atmosphere at a maximum temperature of 1,200°C with a draw ratio of 0.950. The heating rate during the carbonization process was 0.45°C / second. The physical properties of the final carbon fiber 1, which was obtained by surface treatment and sizing agent application to the resulting carbon fibers, are shown in Table 2.
[0133] [Carbon fiber 2-9] Carbon fibers were obtained in the same manner as in Example 1, except that the stretching ratio in the preliminary carbonization process and the stretching ratio, maximum temperature, processing time at the maximum temperature, and heating rate in the carbonization process were changed to those shown in Table 2. The obtained physical properties are shown in Table 2.
[0134] [Carbon fibers 10 and 11] Carbon fibers were obtained in the same manner as in Example 1, except that the single fiber fineness of the carbon fiber precursor fiber bundle was changed to 0.5 dtex or 0.8 dtex, respectively. The obtained physical properties are shown in Table 2.
[0135] [Reference examples 1~3] Flame-resistant fibers were obtained in the same manner as in Example 1, except that the first flame-retardant treatment step was performed under conditions of a flame-retardant treatment temperature of 240°C and a flame-retardant treatment time of 82 minutes, and the second flame-retardant treatment step was performed under conditions of a flame-retardant treatment temperature of 250°C and a flame-retardant treatment time of 85 minutes.
[0136] Infrared spectrum of the fiber after the first flame-retardant treatment process, at 1,370 cm⁻¹-1 1,453 cm⁻¹ for peak intensity -1 The ratio of peak intensities was 0.68. Infrared spectrum of the fiber after the second flame-retardant treatment process at 1,370 cm⁻¹ -1 1,453 cm⁻¹ for peak intensity -1 The peak intensity ratio is 0.50, at 1,370 cm. -1 1,254 cm⁻¹ for peak intensity -1 The ratio of peak intensities was 0.56.
[0137] The obtained flame-resistant fibers were subjected to a pre-carbonization treatment in a nitrogen atmosphere at a maximum temperature of 800°C with a draw ratio of 1.17 to obtain pre-carbonized fibers. The obtained pre-carbonized fibers were then subjected to a carbonization treatment in a nitrogen atmosphere at the maximum temperature and time shown in Table 2, with a draw ratio of 0.980. The heating rate during the carbonization process was 0.35°C / second. The physical properties of the final carbon fibers, obtained by surface treatment and sizing agent application, are shown in Table 2. It was found that simply changing the maximum temperature of the carbonization process, which is generally used to adjust the strand modulus, did not significantly change the strand strength, and that when the strand strength level is high, it is necessary to finely adjust the conditions of the pre-carbonization process and the carbonization process shown in this example.
[0138] [Examples 1-7, Comparative Examples 1-15] The obtained carbon fibers 1-9 and resin compositions 1-6 were combined as shown in Table 3 to fabricate carbon fiber composite materials, and their mechanical properties were measured. The results are shown in Table 3. Although there was a tendency for the 0° tensile strength of the carbon fiber composite material to be higher with higher strand strength of carbon fibers, it was found that this varied significantly depending on the combination with the epoxy resin composition. Furthermore, the elongation of the carbon fiber composite material exceeded 2.3%, and the product of 0° tensile strength and elongation was higher than ever before.
[0139] [Table 1]
[0140] [Table 2]
[0141] [Table 3] [Industrial applicability]
[0142] The carbon fiber composite material of the present invention has high impact resistance and high energy absorption, making it possible to reduce the weight of components even in components where high impact resistance is required.
Claims
1. A carbon fiber composite material comprising: carbon fiber having a strand strength of 7.5 to 8.5 GPa, an elongation of 2.65 to 3.20%, and a single fiber diameter of 4.0 to 6.0 μm; and an epoxy resin composition having an amine-type epoxy resin [A], a thermoplastic resin [B] that dissolves in the epoxy resin, and an epoxy resin curing agent [C], the epoxy resin composition having a degree of cure of 90% or more; and a storage modulus at 275° C. of 1 to 10 MPa as measured in a torsion mode of 1.0 Hz by heating a cured product of the epoxy resin at a rate of 5° C. / min using a dynamic viscoelasticity measuring device in accordance with SACMA SRM 18R-94.
2. The carbon fiber has a strand modulus of 240 to 300 GPa and a strain energy density of 95 J / mm 3 The carbon fiber composite material according to claim 1 .
3. 3. The carbon fiber composite material according to claim 1, wherein a cured product of the epoxy resin composition has a compressive yield stress of 90 to 140 MPa and a compressive yield strain of 10 to 15%.
4. 3. The carbon fiber composite material according to claim 1, having a 0° tensile strength of 4.0 GPa or more and an elongation of 2.5% or more.
5. 3. The carbon fiber composite material according to claim 1, wherein the epoxy resin curing agent [C] is an aromatic amine.